Pengendalian Internal Persediaan Obat di Rumah Sakit Daerah Besemah Kota Pagar Alam - Aldini Nofta Martini; Liza Islamia (LPPM Universitas Lembah Dempo, 2022)
This study aimed to analyze the internal control over the supply of drugs at the Regional Hospital Besemah Pagar Alam. This study is a qualitative research. Sources of data used in this study are primary data and secondary data. Data collection method used is observation, interviews, and documentation. Assessment of the implementation of internal control over drug supply using five components of internal control, namely: environment control, risk assessment, control activities, information and communication, and monitoring. The analysis technique used in this research is descriptive qualitative. The results showed that the internal control over the supply of drugs that are applied at the Regional Hospital Besemah Pagar Alam is adequate overall.